Studies On The Activity Of The Standardized Extracts Of Piper Betle L. And Piper Nigrum L. On Mycobacterium Tuberculosis: Cellular And Metabolomics Approaches - Patilaya, Popi (2012)

(untitled)
The rising of drug-resistance tuberculosis (TB) cases has prompted an urgent need for a new anti-TB drug preferably from local medicinal plants. However, in the last decade not much attention has been given to the microbiology and metabolomics aspects of these plants regarding to their anti-TB activity.